Retrospective Study: Integrating English for Medical Purposes and Edutainment through English-Subtitled K-Drama “Daily Dose of Sunshine” to Enhance Nursing Students’ Psychiatric Vocabulary - Eka Putri, Rahmadila (SALEE: Study of Applied Linguistics and English Education, 2025)
English for Medical Purposes (EMP) focuses on teaching domain-specific vocabulary in clinical settings, including psychiatry. However, psychiatric terminology poses particular challenges for novice nursing students due to linguistic complexity and mental health stigma. To address these issues, this study incorporated the English-subtitled K-Drama “Daily Dose of Sunshine” as an edutainment tool to support vocabulary acquisition and foster more constructive perceptions of psychiatric content. A retrospective descriptive design was employed to analyse existing data from researcher’s previous EMP instructional period at a health-focused higher education institution. This approach aimed to evaluate the pedagogical impact of audiovisual integration in psychiatric English instruction and to generate evidence-based insights for English for Specific Purposes (ESP) practice in researcher’s current vocational context. Data were collected through proportionate stratified sampling of 30 nursing students. The study utilized Likert-scale questionnaire to investigate students’ perceptions of using audiovisual media, Vocabulary Recognition Task (VRT) to measure psychiatric English vocabulary acquisition, and documentation to explore potential patterns between the two datasets. The findings indicated notable vocabulary gains, particularly among students with lower initial proficiency, and improved contextual understanding. These outcomes underscore the potential of edutainment in facilitating domain-specific language learning and reducing stigma. Furthermore, it offers valuable implications for the advancement of ESP instruction in specialized educational contexts.